Development and Usability Testing of HemoGirl, an Android-Based Application for Anemia Education among Adolescent Girls - Annisa Rizkiriani; Hadi Riyadi; Dodik Briawan; Irman Hermadi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Mobile health applications represent an innovative strategy to strengthen health promotion by improving the accessibility and delivery of nutrition-related information, particularly anemia education among adolescent girls. Adolescence is a critical period characterized by increased nutritional demands and vulnerability to iron deficiency anemia, which can adversely affect growth, cognitive performance, and future reproductive health. Given the limitations of conventional educational approaches in engaging adolescents, interactive digital interventions have emerged as a promising alternative. Therefore, this study aimed to develop the HemoGirl mobile application and evaluate its preliminary usability and user acceptance among adolescent girls. Methods: This study employed a Research and Development design using the Waterfall model, encompassing requirement analysis, system design, development, testing, and maintenance. Usability testing was conducted among 61 first-year adolescent girls aged 17–19 years recruited through convenience sampling. Participants attended a supervised usability testing session lasting approximately 60 minutes, during which they used the HemoGirl application and completed predefined tasks before evaluating the system using the System Usability Scale (SUS). The SUS consists of 10 standardized items rated on a five-point Likert scale and assesses usability, ease of use, and user satisfaction. Results: The usability evaluation yielded a mean SUS score of 78 ± 12.7, indicating good usability and acceptable user satisfaction. Participants generally perceived the application as easy to learn, simple to navigate, and appropriate for accessing anemia-related educational content. These findings suggest that the HemoGirl prototype was well accepted by its intended users and met established usability standards. Conclusion: The HemoGirl mobile application demonstrated good usability and user acceptance among adolescent girls. As a prototype for anemia education and self-monitoring, the application shows promise as a digital health promotion tool. However, further longitudinal and experimental studies are required to evaluate its effectiveness in influencing knowledge, health behaviors, and anemia-related outcomes.